effect of Aflatoxin B1-Contaminated Feed on growth AND VITAL ORGANS of advance fry of, Catla catla - S. Andleeb; M. Ashraf; M. Hafeez-ur-Rehman; M. A. Jabbar; F. Abbas; M. Younus (Journal of Animal and Plant Sciences, 2015)
The study was conducted for the period of 90 days to investigate the effect of Aflatoxin B1when present in feed on the growth and histology of advance fry of Catlacatla. The fish was rerered in glass aquaria in Fish Hatchery Complex of the Department. There were 5 treatments and a control with two replicates in each. 180 advance fry were randomly stocked in each glass aquaria. 15 fish per aquaria containing 90 liter fresh clean tubewell water. Five fish were then randomly collected from each aquaria weighed and measured. The prepared feed was divided into 6 equal parts. Part 1 was as control while remaining 5 parts received Aflatoxin in the order of 10, 20, 30, 40 and 50 ppb termed as T1, T2, T3, T4 and T5. Water quality was monitored on daily basis. At the end of the experiment, liver, kidney and intestine were removed for histopathological studies. Results showed that the body weight of advance fry Catlacatla was the highest in control group as compared to aflatoxins treated aquariums. The growth of aflatoxicosed fish was significantly different and lower than control (p< 0.05). Specific growth rate was higher in control aquarium, lowest was in T5 where 50 ppb aflatoxins were applied. Feed conversion ratio was highest in T5 as compared to control. The survival rate was 100% upto T3 while in T4 and T5 was lowest. Weight gain and food conversion ratio (FCR) varied significantly (P<0.05) between control and treatments with diets contaminated with 10 ppb to 50 ppb (AFB1/kg after 90 days). Several histological alterations were recognized in the liver of the fish examined and these were chronic manifestations. Collapsed liver were found in dead fish in T4 and T5. The liver of fishes in T2, T3 and T4 had extensive necrosis, acute cellular swelling or ballooning necrosis, chronic granulomatous inflammation, loss of color where the necrotic tissue becomes paler than the surrounding normal tissue. It is concluded that liver was the principal target organ for aflatoxins. After the invasion of aflatoxins into the liver, lipids infiltrate hepatocytes and leads to necrosis or liver cell death.
Keywords: Aflatoxin B1; contaminated feed; growth; vital organs; Catla catla fry